Trajectory and predictors of HbA1c in children and adolescents with type 1 diabetes—A Danish nationwide cohort study. Issue 6 (11th April 2022) - Ibfelt, Else Helene; Wibaek, Rasmus; Vistisen, Dorte; Andersen, Gregers S.; Jørgensen, Marit E.; Hulman, Adam; Dabelea, Dana; Birkebaek, Niels H.; Svensson, Jannet; Rønn, Pernille F.
Abstract: Objectives: Poor glycemic control in type 1 diabetes increases the risk of chronic complications and it is essential to identify life periods and predictors associated with deteriorating HbA1c . The aim was to describe specific HbA1c trajectories in Danish children and adolescents with type 1 diabetes and study associations with clinical and sociodemographic factors. Research Design and Methods: 5889 children with type 1 diabetes were included from the nationwide Danish Registry of Childhood and Adolescent Diabetes with annual visits during 1996–2019. Trajectories of HbA1c were modeled with linear mixed‐effects models (using age as time scale, included as cubic spline) and with an individual‐specific random intercept and slope. The following cofactors were included stepwise into the model: sex, age at diagnosis, calendar year, parental education, immigrant status, health care region, blood glucose monitoring (BGM) frequency, treatment modalities: continuous subcutaneous insulin infusion (pump) versus multiple daily insulin injection therapy (pen) and continuous glucose monitoring. Results: HbA1c overall increased during age while there was a significant decreasing secular trend. Older age at diagnosis was associated with a steeper trajectory, and non‐Danish origin and shorter parental education were each associated with higher levels of HbA1c across age. A lower BGM frequency was associated with a markedly poorer HbA1c trajectory, while no significant differences were shown for different treatment modalities. Conclusions: Glycemic outcome worsened with age during childhood and adolescence, which is of clinical concern. Important predictors for a poorer glycemic trajectory were later age at diabetes diagnosis, shorter parental education, non‐Danish origin and, in particular low BGM frequency.